Effects of sedentary discontinuous intervention on physiological function and mental health of middle school students - Li, Wanjun; Tang, Qiang; Yan, Xingzhi; Yan, Bingcai (Frontiers in Public Health, 2025)
BackgroundTo explore the effects of sedentary discontinuity on the physical and mental health of middle school students, and to provide reference for improving the health level of middle school students.Methods180 junior high school students were included in this study. The study lasted for one school year. The experimental group added 4 times of 5-8 minutes of physical exercise between classes every day, while the control group arranged the physical exercise between classes independently. Body composition, blood pressure, heart rate variability, diopter and maximum oxygen intake (VO2max) were monitored before and after intervention, and the differences of each index between the two groups and before and after intervention were compared.ResultsBefore intervention, there were no significant differences in body fat percentage (fat%), muscle mass, systolic blood pressure (SBP), diastolic blood pressure (DBP), VO2max, heart rate variability and diopter between 2 groups (P > 0.05). After one academic year of exercise intervention, fat%, SBP, DBP and diopter of the experimental group were lower than those of the control group. VO2max, skeletal muscle mass, RR interval standard deviation (SDNN), root mean square (RMSSD) of the difference between adjacent RR intervals, low-band area (LF) of the area under HRV curve, high-band area (HF) of the area under HRV curve, TP, and sympathetic/vagal balance index (LF/HF) of the experimental group were all higher than those of the control group (P < 0.05). Significant improvements were observed in learning burnout, depression levels, and peer relationships following the intervention.ConclusionThe results of this study suggest that sedentary intermittent intervention can effectively improve the physical health level of adolescents and reduce the risk of cardiovascular disease. Schools should actively carry out physical exercise during recess to help students grow up healthily.